The implementation and utility of clinical exome sequencing in a South African infant cohort - Campbell, L.; Fredericks, J.; Mathivha, K.; Moshesh, P.; Coovadia, A.; Chirwa, P.; Dillon, B.; Ghoor, A.; Lawrence, D.; Nair, L.; Mabaso, N.; Mokwele, D.; et al. (Frontiers in Genetics, 2023)
Genetic disorders are significant contributors to infant hospitalization and mortality globally. The early diagnosis of these conditions in infants remains a considerable challenge. Clinical exome sequencing (CES) has shown to be a successful tool for the early diagnosis of genetic conditions, however, its utility in African infant populations has not been investigated. The impact of the underrepresentation of African genomic data, the cost of testing, and genomic workforce shortages, need to be investigated and evidence-based implementation strategies accounting for locally available genetics expertise and diagnostic infrastructure need to be developed. We evaluated the diagnostic utility of singleton CES in a cohort of 32 ill, South African infants from two State hospitals in Johannesburg, South Africa. We analysed the data using a series of filtering approaches, including a curated virtual gene panel consisting of genes implicated in neonatal-and early childhood-onset conditions and genes with known founder and common variants in African populations. We reported a diagnostic yield of 22% and identified 7 pathogenic variants in the NPHS1, COL2A1, OCRL, SHOC2, TPRV4, MTM1 and STAC3 genes. This study demonstrates the utility value of CES in the South African State healthcare setting, providing a diagnosis to patients who would otherwise not receive one and allowing for directed management. We anticipate an increase in the diagnostic yield of our workflow with further refinement of the study inclusion criteria. This study highlights important considerations for the implementation of genomic medicine in under-resourced settings and in under-represented African populations where variant interpretation remains a challenge.